Implementation of free inquiry approach based on blended learning on creative thinking and student collaboration skills - E. Ernawati; Tri Maniarta Sari (University of Muhammadiyah Malang, 2022)
The free inquiry approach based on blended learning is a learning approach that is carried out by combining face-to-face and online lectures which gives students the freedom to find problems and solve problems independently, design procedures or steps collaboratively by sharing and discussing with friends. Hence, this learning approach is potentially effective in developing critical thinking and students' creativity in solving problems and students' collaborative skills. Based on this, the aim of this research is to see the effect of the free inquiry approach based on blended learning on creative thinking skills and collaboration skills of Biology Education students, Sembilanbelas November Kolaka University. This research uses quasi-experimental Non-equivalent Control Group Design Pretest-Postest Design method. In this design, both the experimental group and the control group were compared where the experimental group was treated with a blended learning-based free inquiry approach, while the control group used a conventional approach (online discussion). The research data were analyzed by descriptive statistics and inferential statistical analysis (t-test) to determine whether there was a difference between the two sample groups studied with a significant level of 0.05. Based on the data analysis, it was found that the free inquiry approach based on blended learning had a better effect on students' creative thinking skills and collaboration skills.